Women's involvement in decision-making and association with reproductive health behaviors: findings from a cross-sectional survey in Niger - Sanyukta Mathur; Karen Kirk; Chaibou Dadi; Leanne Dougherty (BMC, 2024)
Abstract Background Though women in Niger are largely responsible for the familial health and caretaking, prior research shows limited female autonomy in healthcare decisions. This study extends current understanding of women's participation in decision-making and its influence on reproductive health behaviors. Methods Cross-sectional survey with married women (15-49 years, N = 2,672) in Maradi and Zinder Niger assessed women's participation in household decision-making in health and non-health issues. Analyses examined [1] if participation in household decision-making was associated with modern contraceptive use, antenatal care (ANC) attendance, and skilled birth attendance at last delivery and [2] what individual, interpersonal, and community-level factors were associated with women's participation in decision-making. Results Only 16% of the respondents were involved-either autonomously or jointly with their spouse-in all three types of household decisions: (1) large purchase, (2) visiting family/parents, and (3) decisions about own healthcare. Involvement in decision making was significantly associated with increased odds of current modern contraceptive use [aOR:1.36 (95% CI: 1.06-1.75)] and four or more ANC visits during their recent pregnancy [aOR:1.34 (95% CI: 1.00-1.79)], when adjusting for socio-demographic characteristics. There was no significant association between involvement in decision-making and skilled birth attendance at recent delivery. Odds of involvement in decision-making was significantly associated with increasing age and household wealth status, listening to radio, and involvement in decision-making about their own marriage. Conclusion Women's engagement in decision-making positively influences their reproductive health. Social and behavior change strategies to shift social norms and increase opportunities for women's involvement in household decision making are needed. For example, radio programs can be used to inform specific target groups on how women's decision-making can positively influence reproductive health while also providing specific actions to achieve change. Opportunities exist to enhance women's voice either before women enter marital partnerships or after (for instance, using health and social programming).